(untitled) (Epidemiology, Biostatistics, and Public Health, 2024)
Introduction: Despite declining trends in the first two decades of the 21st century, Poland remains a country with relatively high suicide rates. Developing national suicide prevention programmes starts from analysing trends in suicide rates and identifying high risk groups. The aim of this study was to examine suicide epidemiology trends in Poland with a specific focus on age groups and regional differences. Method: This epidemiological analysis examined suicide statistics from 2017 to 2022. We calculated and analysed standardised suicide rates (SDR) across different age groups and regions in Poland using data acquired from Police Headquarters statistics. Percentage changes for the whole study period were determined. Official data on the Polish population was obtained from the Central Statistical Office. Results: Throughout the analysed period, SDR calculated for all ages remained stable, declining by only 2% from 2017 to 2022. The highest SDR were noted in the 55-59 and 60-64 age groups (19,4 and 19,1 per 100 000, respectively, in 2022). Between age groups, notable disparities in trends of changes of SDR values were observed. The greatest increases of 21.6% and 19.6% were noted in the youngest (13-18) and eldest (85+) age groups, respectively. The largest regional increase by 14.4% concerned the Warmian-Masurian region, followed by the Opolskie region by 13.51%. Both regions have some of the lowest GDP values among Polish regions. Conclusion: In Poland suicide rates have increased significantly among adolescents, the eldest and those living in economically disadvantaged regions. The obtained results highlight the need for implementing tailored preventative programmes.